The right to respect for private life in the criminal proceedings - Тракало, Роман Ігорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The issues of respect for the privacy of the criminal proceedings, generalized rules of criminal procedurelegislation of Ukraine and of the solution of the European Court of Human Rights concerning thepermissibility of intervention by the investigating authorities in the privacy of members of the criminalproduction.